Comprehensive Overview of Virtual Power Plants: Integration of Distributed Energy Resources into Power Systems in Terms of Aggregation, Application, and Innovation - Ayhanci, Cihan; Kekezoglu, Bedri; Durusu, Ali (MDPI, 2026)
As modern power systems undergo a paradigm shift toward decentralization, driven by substantial investments in Distributed Energy Resources (DERs), Virtual Power Plants (VPPs) have emerged as the primary mechanism for their effective technical and commercial integration. This paper provides a seminal and comprehensive literature review, dissecting the VPP ecosystem through operational, infrastructural, and coordination strategy perspectives. By categorizing VPPs into distinct technical and commercial frameworks, this study critically evaluates their role in optimizing smart grid components, including demand response, multifaceted market structures, cooperative game-theoretic behaviors, and multi-carrier energy systems. The analysis transcends basic infrastructure, focusing on the resolution of fundamental challenges: mitigating carbon emissions and energy costs, characterizing generation uncertainty and asynchrony, and maintaining the dynamic equilibrium between supply and demand. Furthermore, the review explores advanced strategies for incentivizing prosumer engagement, enhancing market pricing transparency, and ensuring transaction integrity within rigorous operational constraints. A significant methodological evolution is identified, highlighting the transition toward advanced mathematical frameworks and data-driven optimization techniques designed to enhance system resilience and operational stability under multifaceted uncertainties. The synthesis reveals that VPP-led sector coupling integrating electricity, thermal, and hydrogen vectors provides a robust pathway for minimizing grid imbalances and diminishing the overall carbon footprint. By evaluating the subject through a multidimensional lens (technical, economic, environmental, and regulatory) this study serves as a critical reference and strategic roadmap for researchers, planners, and policymakers aiming to navigate the complexities of future smart grids and build a sustainable energy ecosystem.
Keywords: aggregation; carbon emission; carbon mitigation; demand response; Distributed Energy Resources (DERs); multi-energy systems; prosumer engagement; smart grid; uncertainty management; Virtual Power Plant (VPP); DECISION-MAKING; RENEWABLE ENERGY; MANAGEMENT; STRATEGY; MARKET; OPTIMIZATION; UNCERTAINTY; ALGORITHM; DISPATCH; NETWORK; Energy & Fuels